Plato and the poets - Gadamer, Hans-Georg; Mejía, Jorge Mario (Estudios de Filosofía, 1991)
In The Republic, which projects an ideal arrangement of the State and education, Plato has condemned Homer and the great Attic playwrights to exile. Without a doubt, never by a philosopher and so dogmatically has art been denied its rank, never with such scathing has its pretention, so evident to us, to be a manifestation of the deepest and most mysterious truth been challenged. To understand the Platonic criticism of the poets is perhaps the most difficult task that comes in the hardest way to the self-consciousness of the German spirit, posing the discussion with the spirit of antiquity. For it was precisely in ancient art and poetry that the aesthetic humanism of German classicism and romanticism recognized classical antiquity and erected it as a canonical ideal.